Unique New York?: theorizing the impact of resources on the quality of defense representation in a deviant state - Davies, Andrew L. B. (Criminal justice policy review, 2020)
Litigation in New York State has resulted in the allocation of substantial new funding to limit indigent defense caseloads and improve representation provided to criminal defendants. Funding injections have rarely been studied in defense, however, so it is not clear what will be the effects of the new resources. Defense critics expect their impact to be transformative, but empirical scholarship is more pessimistic. We sort between these perspectives using exploratory interviews with the individuals most critical to the planned reforms: executive-level chief public defenders. Conceptualizing defense service quality in terms of “public value,” we find points of deviation from both the optimistic and pessimistic accounts. New York is a “deviant case,” we argue, which can be used to break new theoretical and empirical ground around the question of how resources impact defense service quality.